Age at Work: Explaining variation in frames of older employees in corporate and news media. (2nd September 2017) - Kroon, Anne C.; van Selm, Martine; ter Hoeven, Claartje; Vliegenthart, Rens
Abstract : Despite the fact that workforce aging is recognized as a key social and economic concern of developed countries, previous research has largely neglected the role of corporate and news media in the debate about this topic. Relying on a content analysis of five Dutch newspapers and the corporate media of 50 Dutch organizations ( N  = 1328), this study traces variation in frames of older workers' employability. Results reveal that organizations in their corporate media attempt to avoid associations with problems related to older employees and highlight the solutions they offer, while news media are more inclined to problematize the issue and victimize older employees. This study elucidates our understanding of how corporate and news media communicatively deal with older workers' employability, and how key actors drive frame-formation processes in both domains.